Association between negatively perceived parenting attitudes and dissociation: a cross-sectional study on the general population in Japan - Wang, Baihui; Kuroki, Toshihide (Frontiers in Psychology, 2023)
Objectives Many studies have reported that early traumatic experiences, mainly abuse, are associated with forming dangerous attachments and a contributing factor to dissociation. On the other hand, other studies have investigated the association of non-abusive nurturing and attachment styles with dissociation. The aim of this study is to determine the frequency of dissociative experiences in the general Japanese population and investigate the effects of "overprotection" and "lack of care" as nurturing styles and "abandonment anxiety" and "avoidance of intimacy" as attachment styles on dissociation. Methods A total of 1042 residents aged 18 to 69 years were administered with the Dissociative Experiences Scale (DES), the Japanese version of the WHO-5 Well-Being Index (WHO-5-J), the Parental Bonding Instrument (PBI), and the Experiences in Close Relationships Inventory-the-generalized-other-version (ECR-GO). Hierarchical multiple regression analyses on the effects of "overprotection" and "care" as nurturing attitudes "abandonment anxiety" and "avoidance of intimacy" as attachment styles on dissociation (DES-NDI and DES-T) were conducted. Results Based on the findings of this study, "care" and "overprotection" as nurturing attitudes were shown to be a contributing factor to dissociation (DES-NDI and DES-T). "Avoidance of intimacy" as an attachment style was shown to contribute to pathological dissociation. On the other hand, the influence of attachment style on the relationship between nurturing style and dissociation was not determined. Discussion This study provided essential data on the distribution of dissociative experiences in the general Japanese population. It was indicated that nurturing style, particularly overprotection, may be linked to nonfunctional stress coping and interpersonal anxiety and could be a contributing factor to mental disorders, including dissociation. Furthermore, considering that the effect of nurturing styles on dissociation does not vary with attachment styles, the effect of nurturing styles on dissociation may be more profound.